Adolescent Moral Values: A Qualitative Study in Medan Denai District - Parhusip, Lestari Yunsiska; Daulay, Annisa Arrumaisyah (FORUM PAEDAGOGIK, 2025)
This study aims to understand the role of internalizing religious values in shaping adolescents' moral values, as well as its influence on religious awareness, social behavior, and the quality of interpersonal relationships in the Medan Denai District. The approach used is descriptive-qualitative with purposive sampling techniques targeting adolescents aged 15–18 as the main informants, and parents, teachers, and community leaders as supporting informants. Data were collected through in-depth interviews, participatory observation, and documentation, and then analyzed thematically. Research results show that the internalization of religious values plays an important role in shaping the cognitive, emotional, and social aspects of adolescents' moral values. Cognitively, adolescents are able to distinguish between right and wrong behavior and consider the moral consequences before acting. Emotionally, the practice of worship and participation in routine religious activities help adolescents manage stress, calm themselves, and control their emotions. Socially, internalized religious awareness encourages the formation of discipline, responsibility, social care, as well as the strengthening of harmonious interpersonal relationships based on empathy